Rethinking Thrombolysis in Cerebral Infarction 2b: Which Thrombolysis in Cerebral Infarction Scales Best Define Near Complete Recanalization in the Modern Thrombectomy Era?. Issue 9 (September 2017) - Tung, Eric L.; McTaggart, Ryan A.; Baird, Grayson L.; Yaghi, Shadi; Hemendinger, Morgan; Dibiasio, Eleanor L.; Hidlay, Douglas T.; Tung, Glenn A.; Jayaraman, Mahesh V.
Abstract : Background and Purpose—: Within the thrombolysis in cerebral infarction (TICI) classification, TICI 2b has been historically considered successful recanalization. Recent studies have suggested that TICI 3 and a proposed TICI 2c should be separately reported from TICI 2b, in both the original (>66% reperfusion) and modified (>50% reperfusion) definitions, because of differences in clinical outcomes with greater reperfusion. The purpose of this study was to evaluate differences in early neurological improvement and independence at 90 days using the original TICI, modified TICI, and modified TICI with 2c scales. Methods—: A retrospective review of 129 consecutive patients with middle cerebral artery, M1 segment or intracranial internal carotid artery occlusions. Patient angiograms were graded by 2 experienced readers by percentage recanalization. This was then categorized into original TICI, modified TICI (mTICI), and mTICI with TICI 2c (mTICI 2c) grading scales. Comparison of baseline demographics, early neurological improvement, and independence at 90 days was performed. Results—: A significant difference in early neurological improvement was observed between 2b and 3 ( P =0.032), as well as between 2b and 2c ( P =0.028) under the mTICI 2c grading scale. Similarly, a significant difference in functional independence was observed between 2b and 3 ( P =0.037), as well as between 2b and 2c ( P =0.047) under the mTICI 2c scale. The difference in early neurological improvement or functional independence between 2b and 3 for the original TICI and mTICI scales was not significant. When combining the 2c and 3 groups under the mTICI 2c scale, there were significant differences between 2b and 2c/3 in regards to both early neurological improvement ( P =0.011) and independence ( P =0.018). Conclusions—: Using a TICI grading system that includes an additional category beyond TICI 2b allows for refined prediction of early neurological improvement and functional independence.